PKM Pendampingan Desain Kemasan pada RH (Reta Handycrafts) di Banjar Titih Tengah Kota Denpasar - I Wayan Putu Sucana Aryana; I Wayan Astawa; I Made Adi Suwandana; Agus Wiryadhi Saidi; Siluh Putu Natha Primadewi (Departement of Mathematics Education, 2023)
Packaging design is fundamental for a company because it has a visual meaning that is implied both from the corporate culture, history, and positioning of a company. Every company has a packaging design, some are well-conceived and some are just perfunctory. Maintaining the consistency and quality of the brand image in the minds of consumers is very important so that it is easy to recognize the company in every communication. Products and services that are successful will be satisfying and easy to remember by consumers, as well as the company's brand. The packaging design in which there is a logo makes it the main identity for the launch of a newly established company or new organization. Without a visual identity, it will be difficult for consumers to identify the company. Micro, Small and Medium Enterprises or MSMEs can be interpreted as businesses run by individuals, households, or small-scale business activities that drive the movement of development and the Indonesian economy. According to data from the Cooperatives and UKM Office of the City of Denpasar, for the type of Creative MSMEs, the Micro scale is specifically in the creative field of knitwear craftsmen. RH (Reta Handycrafts) doesn't have a packaging design yet, of course this will cause problems when introducing a product. A product that is sold has more value if it can be packaged very well, but not a few partners ignore it. able to support their business income.